2015
DOI: 10.7202/1028399ar
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of the Japanese beetle, Popillia japonica (Newman) (Coleoptera: Scarabaeidae), to entomopathogenic Hypocreales fungi

Abstract: The susceptibility of adults and larvae of the Japanese beetle to isolates of the fungi Beauveria bassiana, B. brongniartii, Metarhizium anisopliae, Lecanicillium longisporum and L. muscarium (Ascomycota: Hypocreales) was evaluated in laboratory bioassays. The presence of intra- and interspecific variations regarding the pathogenicity of the isolates was investigated. Results show that most of the fungal isolates caused mortality in adults and larvae. Isolates M. anisopliae INRS 705 and B. bassiana INRS 236 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
3
2
Order By: Relevance
“…Our laboratory experiments showed that spray applications of blasto- or conidiospores caused high mortality in adults but not in larvae, independent of the fungal strain. This contrasts previous studies ( 40 , 41 , 58 ); for example, Giroux et al. ( 40 ) found no difference in mortality between adults and larvae of Japanese beetle.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our laboratory experiments showed that spray applications of blasto- or conidiospores caused high mortality in adults but not in larvae, independent of the fungal strain. This contrasts previous studies ( 40 , 41 , 58 ); for example, Giroux et al. ( 40 ) found no difference in mortality between adults and larvae of Japanese beetle.…”
Section: Discussioncontrasting
confidence: 99%
“…This contrasts previous studies ( 40 , 41 , 58 ); for example, Giroux et al. ( 40 ) found no difference in mortality between adults and larvae of Japanese beetle. However, that work used extremely high spore doses ( 40 ), which were 8000 times higher than those used here (10 7 spores mL -1 , which is commonly used in bioassays).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Because of the particular features of this protected area, an eco‐friendly strategy was adopted to control this pest. Entomopathogenic nematodes (EPNs; Heterorhabditidae and Steinernematidae ) have shown greater potential for the biological control of P. japonica compared with other natural biological agents, such as entomopathogenic fungi (eg, Alm, Yeh, Hanula, & Georgis, ; Yeh & Alm, ; Simões et al., ; Morris & Grewal, ; Giorux et al., ; Paoli, Marianelli, Binazzi et al., 2017; Paoli, Marianelli, Torrini et al., ). Generally, Heterorhabditis bacteriophora Poinar, 1976, H. zealandica Poinar, 1990, and Steinernema scarabaei Stock and Koppenhöfer, 2003, proved to be the most effective EPN species against this pest, causing more than 90% mortality in field tests (Grewal, Koppenhöfer, & Choo, and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…Given the current limited distribution of P. japonica in mainland Europe, sustainable and effective containment strategies are essential to limit its spread in newly infested areas (EFSA, 2018). So far, environmentally friendly approaches have been proposed using attract and kill strategies (Marianelli et al, 2018; Paoli et al, 2023), biological control agents such as entomopathogenic nematodes (Marianelli et al, 2018; Mazza et al, 2017; Simões et al, 1993; Torrini et al, 2020) and entomopathogenic fungi (Barzanti et al, 2023; Benvenuti et al, 2019; Giroux et al, 2015). Nevertheless, the integrated pest management approach emphasizes a reduction in the use of synthetic pesticides and is crucial to increase the effectiveness of P. japonica containment with environmentally acceptable alternatives.…”
Section: Introductionmentioning
confidence: 99%